1998
DOI: 10.1128/jvi.72.6.4893-4905.1998
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evolution of the Hypervariable Region of Hepatitis C Virus in a Common-Source-Infected Cohort

Abstract: The long-term evolution of the hepatitis C virus hypervariable region (HVR) and flanking regions of the E1 and E2 envelope proteins have been studied in a cohort of women infected from a common source of anti-D immunoglobulin. Whereas virus sequences in the infectious source were relatively homogeneous, distinct HVR variants were observed in each anti-D recipient, indicating that this region can evolve in multiple directions from the same point. Where HVR variants with dissimilar sequences were present in a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 54 publications
11
55
0
Order By: Relevance
“…It is probable that the high non-synonymous mutation rate re£ects immune pressure exerted as the HVR resulting in the positive selection of persistent variants. Similar immune selection has been found to take place in the V3 loop of gp120 in HIV-1 [20], the tax gene of human T-cell leukemia virus-1 [21], and the HVR in the E2 region of HCV [22,23].…”
Section: Discussionmentioning
confidence: 53%
“…It is probable that the high non-synonymous mutation rate re£ects immune pressure exerted as the HVR resulting in the positive selection of persistent variants. Similar immune selection has been found to take place in the V3 loop of gp120 in HIV-1 [20], the tax gene of human T-cell leukemia virus-1 [21], and the HVR in the E2 region of HCV [22,23].…”
Section: Discussionmentioning
confidence: 53%
“…The vast heterogeneity of the HCV that replicates in an infected patient has been amply documented by molecular cloning and Sanger sequencing and recently by application of ultradeep sequencing (543,584). HCV evolves at rates that are in the range of 10 Ϫ2 to 10 Ϫ3 substitution per site per year (499).…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Known chains of transmission have been used to measure the rate of HIV evolution 57 (BOX 2) and the magnitude of the bottleneck in virus diversity generated at transmission 58 . The Irish anti-D cohort -a well-studied group of HCV-infected women who were accidentally infected with almost identical strains at the same time -has also provided valuable information about variation in viral evolution, host immune selection and disease outcome between patients 59,60 . Using a different HCV transmission cluster, Wrobel et al 61 demonstrated that molecular clock methods can reliably estimate the date that a patient was infected.…”
Section: Known Transmission Historiesmentioning
confidence: 99%